Accepting and Negotiating Service Users' Choices in Mental Health Transition Meetings. (9th June 2014) - Juhila, Kirsi; Hall, Christopher; Günther, Kirsi; Raitakari, Suvi; Saario, Sirpa
Abstract Across Western welfare regimes, policies emphasize that service users should have more choices regarding their services. This article examines how service choices are presented, responded to and decided in interactions between service users and professionals in mental health transition meetings. Choice is often associated with consumerist user involvement ideas, but in mental health choice also relates to the democratic user involvement approach and to shared decision making between professionals and service users. The results of the study show that professionals construct service users as consumers by offering service options in choice making sequences, expecting users to make appropriate choices. Service users mostly act like consumers by responding to these choice options. However, the study also demonstrates that the professionals do not always accept the user's first choice but respond to them as non‐preferred. Sometimes, they also suggest choices on behalf of the users. In these 'non‐accepting' sequences, choices are negotiated in interaction between the parties, rather than users acting as autonomous choice makers. The sequences are based on two kinds of professional reasoning: first, the professional‐led needs assessment and, second, the structure of the service package that the user is being offered. This negotiation has elements of shared decision making and the 'logic of care'. But it also has elements of paternalist control which challenge both consumerist and democratic service user involvement and suggests consideration of more collectively oriented service user actions.